2021
DOI: 10.1002/joa3.12494
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the length of the myocardial sleeve in the superior vena cava in patients with atrial fibrillation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Tsai et al found that SVC initiates AF in 6% of PAF patients and could be effectively and safely ablated with a mean number of five RF applications [ 3 ]. Nyuta et al suggested that SCV length greater than 37 mm and SVC diameter greater than 17 mm could be predictive of SVC foci in AF subjects undergoing PVI [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tsai et al found that SVC initiates AF in 6% of PAF patients and could be effectively and safely ablated with a mean number of five RF applications [ 3 ]. Nyuta et al suggested that SCV length greater than 37 mm and SVC diameter greater than 17 mm could be predictive of SVC foci in AF subjects undergoing PVI [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was further supported by the non-induction of the SVC firing and/or AF initiation by an intravenous administration of isoproterenol (5 μ g) and adenosine triphosphate (30 mg). 9 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, repeated bolus injections of isoproterenol (5 μ g) did not induce extra PV triggers and/or AF initiation. Moreover, intravenous administration of isoproterenol (5 μ g) and adenosine triphosphate (30 mg) 9 did not induce SVC firing and/or AF initiation. During a 30 min observation period, no recurrence of PV-to-atrium conduction was observed.…”
Section: Case Reportmentioning
confidence: 92%
“…A previous study reported that SVC firing is more likely to occur in patients with long SVC sleeves (>37 mm) or long SVC diameters (>17 mm) 19 . Our study also revealed that the longer diameter of the SVC was significantly longer in the SIG (27.4±4.3 vs. 22.9±4.6 mm, p=0.03) compared to that of the non-SIG.…”
Section: Factors Related To Af Originating From the Svcmentioning
confidence: 95%
“…In a report on clinical features, SVC-AF tends to be more common in female patients, those with a lower body mass index, and those with certain genes (rs2634073 and rs6584555) 18 . The electrical characteristics were that SVC-AF is more common in patients with long SVC sleeves (>30 mm 12,13 ), SVC firing is more likely to occur in patients with long SVC sleeves (>37 mm) or long SVC diameters (>17 mm) 19 , and SVC-AF is more common in cases with a large potential (>1 mv 12 ).…”
Section: Factors Related To Af Originating From the Svcmentioning
confidence: 99%